Gambaran Faktor Non-Obstetri Pada Persalinan Prematur di RSUP Prof. Dr. I.G.N.G Ngoerah Denpasar - Aryati, I Gusti Ayu Eka; Ningtyas, Listina Ade Widya; Suindri, Ni Nyoman (Indonesian Health Issue, 2025)
Premature birth is a birth event at a gestational age of <37 weeks which contributes to increasing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). The cause of premature labor is not yet known with certainty, but it is suspected that there are several factors that influence it, one of which is non-obstetric disease. This study aims to determine the description of non-obstetric factors in premature labor at RSUP Prof. Dr. I.G.N.G Ngoerah. This type of research is quantitative descriptive. The research was carried out in November- Desember 2024 with a sample size of 144 respondents using a total sampling technique. Data collection uses secondary data. The results of data analysis obtained from 144 cases of non-obstetric premature births showed 116 cases of non-communicable diseases and 28 cases of infectious diseases. The highest data on non-obstetric premature births were in the non-obstetric non-communicable disease factor of hypertension as many as 49 respondents (42.2%) and the non-obstetric infectious disease factor of STI as many as 16 respondents (57.1%). Pregnant women are expected to undergo routine antenatal check-ups in accordance with the advice of health workers so that non-obstetric risk factors can be identified early to prevent more serious complications for mother and baby.